2022
DOI: 10.3390/ani12141805
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Molecular Study of Cryptosporidium in Preweaned Calves in Kuwait

Abstract: Cryptosporidium is a worldwide enteric protozoan parasite that causes gastrointestinal infection in animals, including humans. The most notable species is Cryptosporidium parvum because of its zoonotic importance; it is also the leading cause of cryptosporidiosis in preweaned calves. A cross-sectional study was conducted to determine the prevalence of Cryptosporidium infection, investigate the potential risk factors, and use molecular diagnosis to identify the predominant Cryptosporidium spp. in preweaned calv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
4
1
Order By: Relevance
“…This finding is consistent with previous studies which reported prevalence rates of 22.5% in Poland [33] and 27.4% in Türkiye [30] for Cryptosporidium infection in calves. However, the infection rate assigned in this study is higher than investigations reported prevalence rates of 18.7% in Jordan [34], 14.7% in Iran [35], 9.7% in Egypt [36], but lower than the reported prevalence rate of 47.9% in Iraq [37], 58.3% in Sudan [38], 84% in Algeria [39], 36.7% in Sweden [40], 33.1% in Kuwait [41], 38.8% in Italy [42], and 53.6% in Türkiye [43]. These variations in the Cryptosporidium infection rates in lambs and calves could be due to geographical differences, farm management, hygiene, agroecological differences, sample size, health situation and diagnostic methods.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…This finding is consistent with previous studies which reported prevalence rates of 22.5% in Poland [33] and 27.4% in Türkiye [30] for Cryptosporidium infection in calves. However, the infection rate assigned in this study is higher than investigations reported prevalence rates of 18.7% in Jordan [34], 14.7% in Iran [35], 9.7% in Egypt [36], but lower than the reported prevalence rate of 47.9% in Iraq [37], 58.3% in Sudan [38], 84% in Algeria [39], 36.7% in Sweden [40], 33.1% in Kuwait [41], 38.8% in Italy [42], and 53.6% in Türkiye [43]. These variations in the Cryptosporidium infection rates in lambs and calves could be due to geographical differences, farm management, hygiene, agroecological differences, sample size, health situation and diagnostic methods.…”
Section: Resultscontrasting
confidence: 86%
“…Similarly, several recent studies in China, India, Malaysia, Australia, Sweden, and Canada, however, have demonstrated the common occurrence of C. bovis and C. ryanae in calves in the absence or low occurrence of C. parvum [54][55][56][57][58]. In contrast, previous studies reported the predominance of C. parvum in calves globally [41,43,59]. This difference in the distribution of Cryptosporidium species in lambs and calves might have resulted from various environmental, host, and management factors.…”
Section: Resultsmentioning
confidence: 89%
“…For example, Cryptosporidium spp. were found in 46.8% in Ningxia, China [ 5 ], 16.20% in India [ 11 ], 35.70% in Vietnam [ 17 ], 33.1% in Kuwait [ 18 ], 24.4% in Taiwan [ 19 ], 5% in Iran [ 20 ], and 4.38% in Guangdong, China [ 21 ]. These data indicate the prevalence of Cryptosporidium in different geographical zones.…”
Section: Discussionmentioning
confidence: 99%
“…So, the calves its age less than six weeks during pre-weaning the C. parvum is the key enteropathogens of neonatal calf led to diarrhea (40). In Kuwait the molecular identification of C. parvum is 62.8% in pre-weaned calves (41).…”
Section: Discussionmentioning
confidence: 99%